Characteristic of Orange Peel Waste-Based on Eco Enzyme at Different Fermentation Duration - Pande Ayu Naya Kasih Permatananda; I Gede Suranaya Pandit (Postgraduate, University of Mataram, 2023)
One effort to overcome the waste problem is by recycling waste into something useful, such as by making eco enzymes that can be used in various fields through fermentation process. The duration of eco enzyme fermentation is determined by the purpose of its production, but most studies require a fermentation duration of 3 months to produce ideal eco enzyme. The raw material used in making eco enzyme in this study is the peel of the Kintamani orange (Citrus nobilis) that widely cultivated in Bali. This study was aimed to examine the differences in the characteristics of eco enzyme based on orange peel waste with different fermentation durations.Â The research method used is experimental. Fermentation was carried out on orange peel waste, brown sugar, and water with a ratio of 3:1:10. Fermentation was carried out at a duration of 10 days, 30 days, 60 days, 90 days. Each eco enzyme with a different fermentation duration was chemically analyzed for PH, TSS, TDS, BOD, COD. The results showed that as the fermentation duration lengthened, there was a decrease in the TSS, TDS, BOD, and COD parameters in orange peel-based eco enzyme, but there was no change in PH. Teen days of fermentation was able to produce eco enzymes with an ideal PH, fresh sour aroma, and high organic content, however, the fermentation did not produce a dark brown color. This research helps in providing reference for the best fermentation duration that need to make eco enzyme.